DNA Fragmentation Index and Male Infertility: A Narrative Review of Mechanisms, Clinical Implications, and Diagnostic Relevance - Abedi, Amir Reza; samenezhad, Sina (Archives of Men's Health, 2025)
Male infertility accounts for approximately half of all cases in couples unable to conceive. Beyond routine semen analysis, sperm DNA integrity measured by the DNA Fragmentation Index (DFI) is emerging as a key indicator of reproductive potential. DFI represents the percentage of sperm with damaged DNA and is associated with poorer reproductive outcomes, including reduced chances of natural conception, ART failure, and increased miscarriage rates. This narrative review examines the biological mechanisms underlying sperm DNA fragmentation, the clinical relevance of DFI in infertility evaluations, available laboratory methods for DFI assessment, and therapeutic strategies. Although interventions like varicocelectomy and antioxidant therapy show promise, the quality of evidence varies. We conclude by discussing current limitations and future directions in this evolving field.